2019
DOI: 10.1002/etc.4442
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Species Sensitivity Distributions to Define Protective Limits for the Use of Organic Wastes as Soil Amendments

Abstract: The use of organic wastes as soil amendments can be an important measure to improve soil quality and reduce waste accumulation and landfilling. However, the potential contaminant loads of such wastes, can be a source of environmental concern. Consequently, legislation has been developed to regulate the use of these wastes in agricultural soils. However, the regulations only consider chemical parameters, which are insufficient to establish the level of environmental risk. A possible solution is the use of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This issue could first be addressed by no longer relating the measured toxic effect to the trace element availability (or that of any other soil contaminant), but rather more empirically relating it to the soil OW application rate. Application of this strategy in RA and LCIA has been supported by the findings of Pandard and Römbke (2013), Huguier et al (2015), Pivato et al (2015) and Renaud et al (2019). This issue could alternatively be addressed by relating trace element exposure to trace element bioaccumulation in soil organisms, since this bioaccumulation is considered as a prerequisite for any toxic effect.…”
Section: Influence Of Soil Organisms On Trace Element Availability An...mentioning
confidence: 95%
See 3 more Smart Citations
“…This issue could first be addressed by no longer relating the measured toxic effect to the trace element availability (or that of any other soil contaminant), but rather more empirically relating it to the soil OW application rate. Application of this strategy in RA and LCIA has been supported by the findings of Pandard and Römbke (2013), Huguier et al (2015), Pivato et al (2015) and Renaud et al (2019). This issue could alternatively be addressed by relating trace element exposure to trace element bioaccumulation in soil organisms, since this bioaccumulation is considered as a prerequisite for any toxic effect.…”
Section: Influence Of Soil Organisms On Trace Element Availability An...mentioning
confidence: 95%
“…The authors also suggested to further reduce this PNECSoil by a dimensionless assessment factor, depending on the number of trophic levels assessed, the timespan of the exposure to OW-amended soil (short-term/acute vs. long-term/chronic), and on whether the ecotoxicological RA were performed on laboratory or field data. Renaud et al (2019) recently proposed to refine the rendition of dose-response curves obtained from OW-amended soils by establishing a species sensitivity distribution for each tested OW. These species sensitivity distributions are based on ecotoxicological endpoints determined for several species (e.g.…”
Section: Ecological and Human Risks Due To Ow-borne Trace Elementsmentioning
confidence: 99%
See 2 more Smart Citations